Formation mechanism and regulation analysis of trumpet leaf in Ginkgo biloba L - Li, Xin-hui; Kang, Xiao-jing; Zhang, Xin-yue; Su, Li-ning; Bi, Xing; Wang, Rui-long; Xing, Shi-yan; Sun, Li-min (Frontiers in Plant Science, 2024)
The research of plant leaf morphology is of great significance for understanding the development and evolution of plant organ morphology. Ginkgo biloba L, being a relict plant, generally displays bilobed and flat leaf morphology. However, throughout the long historical evolution process, the leaves have undergone a rich variety of variations. This study investigated the distinct "trumpet" leaves and normal fan-shaped leaves of G. biloba. Through phenotypic and photosynthesis analyses, and anatomical observations, it was revealed that trumpet-shaped G. biloba had fewer cells in its leaves. The morphological differences between the dorsal and abdominal epidermal cells were obvious. The net photosynthetic rate was significantly reduced. Moreover, utilizing transcriptomic and metabolomic analyses, the research unveiled the involvement of endogenous plant hormones such as GA, auxin, and JA as well as metabolites such as flavonoids and phenolic acids in the formation of trumpet-shaped G. biloba leaves. These results highlight the participation of plant endogenous hormones, particularly auxin, GA, and flavonoid metabolites, in shaping trumpet-shaped leaves of G. biloba. The results of this study uncovered the involvement of various key biological processes and gene expression regulations in the trumpet-shaped leaves of G. biloba. It offers a fresh perspective for understanding plant leaf development. Additionally, it holds substantial significance for the selection and development of ornamental G. biloba varieties.